Step
*
1
of Lemma
bag-subtract-no-repeats
1. T : Type
2. eq : EqDecider(T)
3. bs : bag(T)
4. as : bag(T)
5. bag-no-repeats(T;bs)
⊢ bag-no-repeats(T;bag-subtract(eq;bs;as))
BY
{ (MoveToConcl (-3) THEN (BagInd (-1) THENA Auto) THEN Reduce 0 THEN (UnivCD THENA Auto)) }
1
1. T : Type
2. eq : EqDecider(T)
3. bs : bag(T)
4. bag-no-repeats(T;bs)
⊢ bag-no-repeats(T;bag-subtract(eq;bs;[]))
2
1. T : Type
2. eq : EqDecider(T)
3. u : T
4. v : T List
5. ∀bs:bag(T). (bag-no-repeats(T;bs) 
⇒ bag-no-repeats(T;bag-subtract(eq;bs;v)))
6. bs : bag(T)
7. bag-no-repeats(T;bs)
⊢ bag-no-repeats(T;bag-subtract(eq;bs;[u / v]))
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  bs  :  bag(T)
4.  as  :  bag(T)
5.  bag-no-repeats(T;bs)
\mvdash{}  bag-no-repeats(T;bag-subtract(eq;bs;as))
By
Latex:
(MoveToConcl  (-3)  THEN  (BagInd  (-1)  THENA  Auto)  THEN  Reduce  0  THEN  (UnivCD  THENA  Auto))
Home
Index